2008
DOI: 10.1371/journal.pgen.1000190
|View full text |Cite
|
Sign up to set email alerts
|

The Histone H3K79 Methyltransferase Dot1L Is Essential for Mammalian Development and Heterochromatin Structure

Abstract: Dot1 is an evolutionarily conserved histone methyltransferase specific for lysine 79 of histone H3 (H3K79). In Saccharomyces cerevisiae, Dot1-mediated H3K79 methylation is associated with telomere silencing, meiotic checkpoint control, and DNA damage response. The biological function of H3K79 methylation in mammals, however, remains poorly understood. Using gene targeting, we generated mice deficient for Dot1L, the murine Dot1 homologue. Dot1L-deficient embryos show multiple developmental abnormalities, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
408
6
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(443 citation statements)
references
References 34 publications
27
408
6
2
Order By: Relevance
“…27,28 At E15.5, we find that H3K79me3 is more abundant in maturing inner cortical tubules than nascent nephrons or cap mesenchyme (Fig. 7A-C).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…27,28 At E15.5, we find that H3K79me3 is more abundant in maturing inner cortical tubules than nascent nephrons or cap mesenchyme (Fig. 7A-C).…”
Section: Resultsmentioning
confidence: 87%
“…47 Indeed, Dot1l-knockout mice die at E10.5 from cardiovascular defects and severe anemia. 28 The function of Dot1l in the developing kidney is unknown but it has been suggested that Dot1l-H3K79 methylation plays a role in terminal differentiation of the collecting duct. 48 Histone methylation occurs on lysine and arginine residues.…”
Section: Discussionmentioning
confidence: 99%
“…Kmt4-depleted ESCs appear to self-renew with pluripotency markers expressed but have a lower proliferation rate [122]. Kmt4 deletion in ESCs also leads to the loss of H3K9me2 and H4K20me3 at centromeres and telomeres, resulting in a less condensed chromatin state [122].…”
Section: Wwwcell-researchcom | Cell Research Gaoyang Liang and Yi Zmentioning
confidence: 99%
“…*Enhanced effi- [197]; defect in neur- [197] ciency by Kmt1c oectoderm contribution inhibitor [73] in teratoma [46] Kmt1d/ NA Reduced NA NA Postimplantation Ehmt1/ efficiency [74] lethality (E8.5-9.5) Glp1 [197] Kmt1e/ NA Reduced Failure and acquiIncorporation to trophe-Peri-implantation Eset/ efficiency [74] sition of trophectctoderm upon blastocyst lethality (E3.5-5.5) the requirement growth rate [122] of Klf4 [74] [122]…”
Section: Introductionmentioning
confidence: 99%
“…126 However, safety studies are warranted, as genetic disruption in mice results in embryonic lethality. 127 Several downstream targets of the MLL-fusion complex could be possible targets of MLL-rearranged AML. Upregulation of HOX genes is one of the most important hallmarks of MLL-rearranged leukemias.…”
Section: Toward Targeted Therapymentioning
confidence: 99%